FAKTOR-FAKTOR PENYEBAB KETERLAMBATAN PROYEK RENOVASI DAN PERLUASAN GEDUNG BALAI KARANTINA IKAN AMBON - Kopong, Legion; Maelissa, Nelda; Titaley, Henriette Dorothy (Journal Agregate, 2023)
Conatruction dealy is acommon problem Which frequently happens in construction industry. The purpose of this study was to indentity and categorize the delays causing factors greatly effecting the fish quarantine center building revavation and expansion project. The Fish quarantine center building renovation project was the object of this study motivated by delays. Futhermore, based on the secondary data obtained, time schedule is entirely used as the duration and normal cost of the project. Then, the Principal Compenent Analysis (PCA) method is applied to be able to find out the main factors causing dealys. Based on the results of the normality test and principal compenent analysis, the factors that effect the delay in the renovation and expansion of the Ambon Fish Quarantine Center Building were the material factors with a total variance of 57.575% including X1.1. Lack of construction materials, X1.2 Material changes in from, function, and specifications, X1.3 Delay in delivery of materials, X1.4 Damage to materials in storage, X1.5 Inccuracy of time.